RESEÑA de: European Comission. Key topies in Volume 1: Financial supportt for students in higher education in Europe: Trends and debates. Luxemburgo: Office for Official Publicatíons of the European Communities, 1999 - Arrimadas Gómez, Irene (Revista Española de Educación Comparada, 1999)
-